TESTOSTERONE TO ESTRADIOL RATIO IS A DIFFERENTIAL FEATURE BETWEEN GOOD AND POOR LIBIDO CROSSBRED BULLS - SINGH, K; KUMAR, A; HONPARKHE, M; MALHOTRA, P (The Indian Journal of Animal Reproduction, 2016)
Forty-five crossbred bulls were categorized into good (n=20) and poor libido (n=25) on the basis of their reaction time (good 3 min). Serum prolactin and thyroid hormone profile was similar (p>0.05) in both the categories, whereas, serum testosterone was high (p
Keywords: Bulls; Libido; Estradiol; Testosterone; Thyroid hormone; Prolactin